The acute effect of dynamic warm-up at different intensities for jumping performance - Muhammad Al-Basit Fahmi Jasli; Nor Fadila Kasim; Fairus Fariza Zainudin (Sriwijaya Journal of Sport, 2024)
Background Problems: Warm-up is carried out before exercise to prevent injuries and optimize the subsequent exercise performance. The warm-up intensity for jumping performance should focus on preparing the body for explosive movements while minimizing the risk of injury. A well-designed warm-up routine can improve jump performance, increase flexibility, and enhance muscle activation. Research Objectives: This study aims to identify the effect of warm-up at 60%, and 80% heart rate on jumping performance, 0 minutes rest, 10 minutes rest, and 20 minutes rest. Methods: 10 male athletes (age = 22.40 ± 1.42 years and BMI = 24.28 ± 2.15) were involved in this study. Each participant was required to perform 3 types of warm-ups: 60% heart rate, 80% heart rate, and control. Jumping performance was measured immediately after warm-up and post-warm-up at 10 and 20 minutes. All measurements were carried out on a different day to avoid bias. Finding/Results: The results show that there is no significant difference in intensity at 0 minutes, 10 minutes, and 20 minutes post-warm-up and no significant difference in jumping performance across all intensities at 60% heart rate, 80% heart rate, and control group. Conclusion: These findings suggest that DWU may not have a significant effect on acute jumping performance. It is suggested that future researchers investigate different warm-up protocol options and use a bigger sample size to better understand how warm-up intensity affects jumping performance.